2015
DOI: 10.1212/wnl.0000000000001831
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathologies are common and related to dementia in the oldest-old

Abstract: Objective: The purpose of this study was to examine the role of multiple pathologies in the expression of dementia in the oldest-old.Methods: A total of 183 participants of The 901 Study with longitudinal follow-up and autopsy were included in this clinical-pathologic investigation. Eight pathologic diagnoses (Alzheimer disease [AD], microinfarcts, hippocampal sclerosis, macroinfarcts, Lewy body disease, cerebral amyloid angiopathy, white matter disease, and others) were dichotomized. We estimated the odds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
213
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(239 citation statements)
references
References 38 publications
21
213
1
4
Order By: Relevance
“…In 2015, it was shown that the presence of multiple pathologic diagnoses occurred more frequently in those with dementia compared with those without dementia in 183 participants of the 901 Study. 23 Despite support for the significance of comorbid neuropathologic abnormalities in dementia in older adults, a large-scale comprehensive examination of their frequencies and overall neurocognitive effects has not yet been reported. Here we address this gap by parallel analyses in 2 distinct population-based brain autopsy panels, the predominantly Caucasian NS women and the Japanese American HAAS men.…”
mentioning
confidence: 99%
“…In 2015, it was shown that the presence of multiple pathologic diagnoses occurred more frequently in those with dementia compared with those without dementia in 183 participants of the 901 Study. 23 Despite support for the significance of comorbid neuropathologic abnormalities in dementia in older adults, a large-scale comprehensive examination of their frequencies and overall neurocognitive effects has not yet been reported. Here we address this gap by parallel analyses in 2 distinct population-based brain autopsy panels, the predominantly Caucasian NS women and the Japanese American HAAS men.…”
mentioning
confidence: 99%
“…The prevalence studies must be interpreted cautiously since aged subjects with and without dementia show a high frequency of mixed pathologies [18][19][20][21][22].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Проведенные недавно эпидемиологические исследования «80+» и «90+» показали [18], что зависи-мость развития БА от возраста не является линейной. Так, действительно, частота развития БА увеличивается с возраста 50 до 75-80 лет; у людей старше 80 и тем более старше 90 лет частота распространения БА, напротив, снижается.…”
unclassified